Ectopic Pregnancy and Assisted Reproductive Technologies: A Systematic Review - Velalopoulou, Anastasia; Peschos, Dimitrios; Ospan, Mynbaev; Marina, Eliseeva; Verginadis, Ioannis; Simos, Yannis; Panagiotis, Tsirkas; Karkabounas, Spyridon; Kalfakakou, Vicky; Evangelou, Angelos; Kosmas, Ioannis P. (IntechOpen, 2011)
None